Categorial shift via aspect and gender change in deverbal nouns. (May 2019) - Iordăchioaia, Gianina; Werner, Martina
Abstract: In this paper we are concerned with the effects of categorial shift on action deverbal nouns formed by means of the suffix - ing in English and its counterpart - ung in German in the history of the two languages. While the two cognate suffixes exhibit similar degrees of categorial shift in terms of the coarse properties that they preserve from the base verbal category or acquire from the new nominal category, they turn out to exhibit opposite preferences with respect to the aspectual value of the base verb that they attach to, with subtle correlated effects in their morphosyntactic and semantic behavior. Specifically, - ing derives action nominals that highlight a process reading, while - ung is restricted to telic verbs and contributes a result reading. We show that at earlier stages of the two languages, the two suffixes were aspectually more flexible. We explain the present-day contrast through internal and external factors that relate to the competition with newly emerging suffixes, but also to the different evolution of grammatical gender in the two languages and its impact on the countability properties of derived nouns. We conclude that in its evolution - ung completed the full cycle of categorial shift of an action nominalization, while - ing remains slightly closer to the original verbal category due to its process-oriented interpretation. Highlights: Cognate English ing and German ung nominalizing suffixes differ aspectually This aspectual difference brings ing closer to verbs and ung closer to nouns. At older language stages ing and ung were similarly flexible in interpretation. Historically, the competition with other nominalizations triggered this change. The second factor was the different evolution of gender in English vs. German.